ANALISIS PERBANDINGAN VOLUME PENJUALAN MENGGUNAKAN STRATEGI PEMASARAN OFFLINE DAN ONLINE TERHADAP PERTUMBUHAN LABA DI MASA PANDEMI COVID-19 (PADA USAHA KONVEKSI BAROKAH DI KABUPATEN TULUNGAGUNG) - Dewi, Nova Artika; Luayyi, Sri; Attarie, Prima Noermaning (Jurnal Ilmiah Cendekia Akuntansi, 2022)
Barokah Convection is one of the businesses engaged in the manufacture of mukena and koko clothes. The purpose of this research is to compare sales volume using offline and online marketing strategies to profit growth during the covid-19 pandemic. The data analysis technique used in this study is a quantitative descriptive analysis technique. The source of data in this study is primary data. The results showed that based on both marketing strategies, sales volume with offline marketing was always higher. In 2019, the sales volume at Barokah convection was Rp. 1,070,130,000, while with online marketing the sales volume is only Rp. 501.100.000. In 2020, sales volume decreased due to the COVID-19 pandemic. The offline sales volume in 2020 is Rp. 880.910.000, while the online sales volume was not higher at Rp. 490,315,000. The resale volume has increased in 2021. The offline sales volume in 2021 is Rp. 1,065,480,000, while the online sales volume was not higher at Rp. 469,300,000. Based on the two marketing strategies used, profit growth with offline marketing in 2020 decreased by -27.8% and in 2021 increased to 36.0%. Profit growth with online marketing in 2020 decreased by -5.6% and fell again in 2021 by -3.9%. Keyword : Sales Volume, Profit Growth